Epidemiological profile and effectiveness of immediate postpartum contraception in Brazilian women - Steiner, Marcelo Luis; Mendes, Julia Lorenzini; Strufaldi, Rodolfo; Carneiro, Monica; Giovanelli, Silvana Aparecida; da Silva, Mariliza Henrique (Frontiers in Global Women's Health, 2023)
Purpose To determine the epidemiological profile of women who inserted copper intrauterine device (Cu-IUD), subdermal etonogestrel implant (ENG), tubal ligation (TL), depot medroxyprogesterone acetate (DMPA) or did not choose a contraceptive method (NCM) in the immediate postpartum period and compare the contraceptive effectiveness of Cu-IUD and DPMA with non-MAC. Methods We analyzed the epidemiological profile of women who inserted copper intrauterine device (Cu-IUD), subdermal etonogestrel implant (ENG), tubal ligation (TL), depot medroxyprogesterone acetate (DMPA) or did not choose a contraceptive method (NCM) in the immediate postpartum. The data was collected by electronic medical records of postpartum women assisted at the University Hospital of São Bernardo do Campo (HMU-SBC) from January 2016 to December 2020. Also, we compared the contraceptive effectiveness of Cu-IUD and DPMA with non-MAC by identifying women who returned for second delivery during the study period and analyzing the contraceptive method chosen in the first hospitalization. Then the pregnancies interval and the sociodemographic characteristics were analyzed according to contraceptive method type. Results Data from 20,896 women were collected, of which 8,183 (39%) opted for Cu-IUD, 559 (2.5%) DPMA, and 10,989 (52.5%) chose not to use contraception at the time of hospital discharge. When comparing these groups, women in the DPMA were younger (26.5 ± 7.3, p < 0.05), and NCM showed women with a lower number of pregnancies (2.2 ± 1.3, p < 0.05). Subjects in the TL group (4.6%) had the higher number of pregnancies (3.8 ± 1.2, p < 0.05), and ENG group, the highest number of miscarriages (1.6 ± 1.3, p < 0.05). Of those women who returned pregnant, 5.5% belonged to the DPMA group, 6% to the NCM group, and 2.3% to the Cu-IUD. Conclusions Women who opted for Cu-IUD insertion were younger, had more pregnancies and vaginal delivery when compared to those who did not choose a method. Of those women who returned, the minority opted for Cu-IUD compared to those that opted for DPMA or no method.